Proceedings of the 18th Annual International Conference on Supercomputing 2004
DOI: 10.1145/1006209.1006243
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive java optimisation using instance-based learning

Abstract: This paper describes a portable, machine learning-based approach to Java optimisation. This approach uses an instancebased learning scheme to select good transformations drawn from Pugh's Unified Transformation Framework [11]. This approach was implemented and applied to a number of numerical Java benchmarks on two platforms. Using this scheme, we are able to gain over 70% of the performance improvement found when using an exhaustive iterative search of the best compiler optimisations. Thus we have a scheme th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…However, the interplay of such optimisations combined with the complexity and variety of target platforms often renders static mapping approaches far less effective than the mappings that can easily be achieved manually. Even in the single-processor setting it has been shown that semi-static approaches such as iterative optimisations [47,54] can improve the effectiveness of the optimisation process. The ParaPhrase approach avoids these problems by exploiting a more dynamic approach that can adapt to changing system conditions, given a good initial placement as its starting point.…”
Section: Related Workmentioning
confidence: 99%
“…However, the interplay of such optimisations combined with the complexity and variety of target platforms often renders static mapping approaches far less effective than the mappings that can easily be achieved manually. Even in the single-processor setting it has been shown that semi-static approaches such as iterative optimisations [47,54] can improve the effectiveness of the optimisation process. The ParaPhrase approach avoids these problems by exploiting a more dynamic approach that can adapt to changing system conditions, given a good initial placement as its starting point.…”
Section: Related Workmentioning
confidence: 99%
“…He developed the GAPS framework [87] which used a genetic algorithm to traverse a search space of affine schedules for automatic parallelization. In addition, Long and O'Boyle [80] considered a search space of transformation sequences represented in the UTF framework [63]. Both of these approaches suffer from under-constraining the search space by considering all possible schedules, including illegal ones.…”
Section: Related Workmentioning
confidence: 99%
“…Our contribution is to reconcile fine-grain control of transformation heuristics -as opposed to optimization flag or pass selection [109,3] -with the guaranteed legality of the transformed program -as opposed to filtering approaches [87,80,81] or always-correct transformations [107,71].…”
Section: Evolutionary Traversal Of the Polytopementioning
confidence: 99%
See 1 more Smart Citation
“…Logistic regression is used in [7] to derive a predictive model that selects suitable optimizations to apply to each method based on code features. Instance-based learning is used in [13] to select suitable loop transformations within an optimization space of various loop re-ordering transformations.…”
Section: Related Workmentioning
confidence: 99%